Nonalcoholic Fatty Hepatitis: An Important Clinical Condition - Samuel W. French; Leslie B. Eidus; J. Freeman (Canadian Journal of Gastroenterology)
The entity fatty hepatitis is defined and the literature characterizing the clinical settings in which it develops is reviewed. The pathogenesis is discussed with emphasis on the common denominators shared by the various clinical conditions with which it is associated. The roles of alcohol, obesity and type II diabetes are stressed where inhibition of fatty acid oxidation by the liver is the basic defect in metabolism leading to fatty change, balloon degeneration and Mallory body formation. It is concluded that this important entity is more common than is generally appreciated.